2021
DOI: 10.1371/journal.pone.0245966
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety culture and associated factors among health care professionals at public hospitals in Dessie town, north east Ethiopia, 2019

Abstract: Introduction Patient safety culture is defined as the attitudes, perceptions, and values that staffs share within an organization related to patient safety. The safety of health care is now a major global concern. It is likely that millions of people suffer disabling injuries or death directly related to medical care. Particularly in developing and transitional countries, patient harm is a global public health problem. The objective of the study is to assess patient safety culture and associated factors among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
29
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 14 publications
(19 reference statements)
8
29
2
1
Order By: Relevance
“…Apart from these differences in the early years, we found that the perception of PSC was related to age: the more senior, the more positive. This is in agreement with the findings of Mohammed et al 28…”
Section: Discussionsupporting
confidence: 94%
“…Apart from these differences in the early years, we found that the perception of PSC was related to age: the more senior, the more positive. This is in agreement with the findings of Mohammed et al 28…”
Section: Discussionsupporting
confidence: 94%
“…The section that deals with descriptive cross-sectional quantitative studies have sections that assess the relevance of the sampling to the research question, the representative of the sample to the target population, appropriateness of the measurements, the risk of nonresponse is low, and whether the statistical method adopted responded appropriately to the research question. All the studies identified in this category had all the responses being affirmative to each type except three [14,[16][17][18][19][20][21][22][23][24][25][26]. The three studies failed to meet the criteria requiring the study sample to represent the population [17,19,26].…”
Section: Quality Appraisalmentioning
confidence: 99%
“…The study approaches were qualitative [19,28], quantitative [14,16,17,[20][21][22][23][24][25][26]31], and intervention studies [29]. The specific study designs were cross-sectional [14, 16, 17, 19-24, 26-28, 31], descriptive correlational [25], randomized control trial [29] as shown in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that several studies have been conducted in the eld of safety culture in general and in the emergency department around the world including Iran Healthcare system [1, 16-18] and its relationship with job satisfaction of the healthcare specialists and adverse events [11,16,19,20], there is limited number of studies that have investigated the emergency nurses' perception of patient safety culture and its relationship with job satisfaction and adverse events at university hospital's emergency departments. Working in Emergency department requires relatively special skills and commitments [21]. Therefore, it has a signi cant importance to study the patient safety culture among the emergency department's health care professionals especially among the emergency nurses.…”
Section: Introductionmentioning
confidence: 99%